Advancing Research Models and Technologies to Overcome Biological Barriers to Plasmodium vivax Control. Issue 2 (February 2018) - Armistead, Jennifer S.; Adams, John H.
Abstract : Malaria prevalence has declined in the past 10 years, especially outside of sub-Saharan Africa. However, the proportion of cases due to Plasmodium vivax is increasing, accounting for up to 90–100% of the malaria burden in endemic regions. Nonetheless, investments in malaria research and control still prioritize Plasmodium falciparum while largely neglecting P. vivax . Specific biological features of P. vivax, particularly invasion of reticulocytes, occurrence of dormant liver forms of the parasite, and the potential for transmission of sexual-stage parasites prior to onset of clinical illness, promote its persistence and hinder development of research tools and interventions. This review discusses recent advances in P. vivax research, current knowledge of its unique biology, and proposes priorities for P. vivax research and control efforts. Trends: The predilection of P. vivax for immature red blood cells (RBCs), its ability to form hypnozoites, and early transmission of gametocytes are significant barriers to research and control. Improved understanding of the preferred host cell for P. vivax invasion (reticulocytes expressing high levels of CD71) has enabled development of ex vivo assays and short-term growth, but long-term continuous culture remains elusive. Nonhuman primates (NHPs) remain the best model for P. vivax research, but controlled human malaria infections (CHMIs), and pending further studies, humanized mice are promising alternatives. In-depth genomics and systems biology approaches have provided new insight into P. vivax genetics, RBC invasion, multigene families, evolution, drug resistance, and relapse. Genetic modification of P. vivax remains challenging, but successes with P. cynomolgi and P. knowlesi may provide insight necessary to achieve this goal.